Why Do I Feel More Confident? Bandura's Sources Predict Preservice Teachers' Latent Changes in Teacher Self-Efficacy - Pfitzner-Eden, Franziska (Frontiers in Psychology, 2016)
Teacher self-efficacy (TSE) is associated with a multitude of positive outcomes for teachers and students. However, the development of TSE is an under-researched area. Bandura (e.g., 1997) proposed four sources of self-efficacy: mastery experiences, vicarious experiences, verbal persuasion, and physiological and affective states. This study introduces a first instrument to assess the four sources for TSE in line with Bandura’s conception. Gathering evidence of convergent validity, the contribution that each source made to the development of TSE during a practicum at a school was explored for two samples of German preservice teachers. The first sample (N = 359) were beginning preservice teachers who completed an observation practicum. The second sample (N = 395) were advanced preservice teachers who completed a teaching practicum. The source measure showed good reliability, construct validity, and convergent validity. Latent true change modeling was applied to explore how the sources predicted changes in TSE. Three different models were compared. As expected, results showed that TSE changes in both groups were significantly predicted by mastery experiences, with a stronger relationship in the advanced group. Further, the results indicated that mastery experiences were largely informed by the other three sources to varying degrees depending on the type of practicum. Implications for the practice of teacher education are discussed in light of the results.